A Distinguishing Artistic Feature of the Novel a Handful of Rice: Exploring Rural-Urban Dichotomy in A Handful of Rice (Journal of Advances and Scholarly Researches in Allied Education, 2016)
A distinguishing artistic feature of A Handful of Rice is the successful operation of the system of parallels and contrasts. In this novel there is juxtaposition of the rural life and urban life. Ravi leaves the penury and apathy of his village in utter despair hoping to make a better living in the city. But he is equally disappointed here. The ‘arid dump’ of the village is now replaced by the ‘Jungle’ of the city. Ravi thinks that the modern city is “a man-made Jungle…full of snares and traps.”